Assessment of Pattern of Drug Abuse from Different Clinical Settings in a Reference Laboratory of Pakistan During the COVID-19 Pandemic - Alveena Younas; Muhammad Aamir; Sobia Irum Kirmani; Zujaja Hina Haroon; Afshan Bibi; Muhammad Usman Munir (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the pattern of drug abuse from different clinical settings in a reference laboratory of Pakistan during the COVID-19 pandemic and assess any change from the previous trend.